Monolithic noble metal catalyst as well as preparation method and application thereof
By regulating the surface defect structure of the catalyst and the dispersion of precious metals, the problems of high usage, high cost and poor stability of precious metals are solved, and the effect of efficient removal of carbon-based oxygen-containing molecular gases and improving catalytic oxidation efficiency is achieved.
Patent Information
- Application Number
- CN202311165148.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-11
AI Technical Summary
In the existing catalytic oxidation technology, the problems of high usage, high cost and poor stability of precious metals have not been effectively solved, resulting in a decrease in activity and high cost of catalysts during use.
By regulating the surface defect structure of the integral catalyst, the dispersion and active phase exposure of active precious metals are promoted, while reducing the precious metal content, the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen is increased, and the catalytic efficiency of the catalyst is improved.
It has achieved efficient removal of carbon-based oxygen-containing molecular gases in the exhaust gas during chemical production, improved catalytic oxidation efficiency, reduced operating costs, and improved the stability and applicability of the catalyst.
Smart Images

Figure CN119608155A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and specifically to an integral noble metal catalyst and a preparation method and application thereof, and more specifically to an integral carbon-based oxygen-containing small molecule gas oxidation removal catalyst and a preparation method thereof and application thereof in catalytic oxidation of carbon-based oxygen-containing small molecule gases. Background Art
[0002] In the petrochemical production process, carbon-based oxygen-containing small molecule gases often undergo incomplete reactions during the directional oxidation process, resulting in the enrichment of oxygen-containing small molecule gases in the exhaust gas discharged from the device or the circulating carrier gas, which not only causes the risk of explosion in the chemical production process, but also forms photochemical phenomena, causing pollution to the surrounding environment. At present, the main treatment method for oxygen-containing small molecule exhaust gas discharged from the oxidation process of petrochemical devices is catalytic oxidation. Catalytic oxidation can completely oxidize oxygen-containing small molecule gases to form carbon dioxide. At the same time, in order to meet the requirements of low pressure drop and large air volume conditions, the current catalytic oxidation method generally uses a monolithic catalyst loaded with precious metals. However, the problems of large amount of precious metals, high cost and poor stability still exist.
[0003] At present, catalytic oxidation methods generally use catalysts with active metals loaded on carriers. Usually, the carriers are in the form of silica gel, activated alumina, glass fiber mesh (cloth), hollow ceramic balls, sea sand, layered graphite, hollow glass beads, quartz glass tubes (sheets), ordinary (conductive) glass sheets, organic glass, optical fibers, natural clay, foam plastics, resins, sawdust, expanded perlite, activated carbon, etc. Different carriers have different loading amounts of active metals. However, the problems of large active metal usage, high cost and poor stability still exist.
[0004] Patent application CN113996284A discloses a method for preparing a low-temperature catalytic oxidation catalyst for carbon monoxide. A simple impregnation method is used to impregnate diatomite with cerium nitrate ethanol solution, followed by drying and calcination to prepare a new CO catalytic oxidation catalyst loaded with CeO2 on diatomite, which exhibits good catalytic activity in CO catalytic oxidation experiments. However, the catalyst needs to be loaded with a large amount of active precious metals during the preparation process, and low specific surface area CeO2 / Fe2O3 is added during the preparation of the monolithic catalyst, resulting in poor dispersion of the active metal when loaded and low effective utilization rate.
[0005] Patent application CN114308063A discloses a PtCo / Co3O 4x Al2O3 multi-interface structure catalyst and its preparation method and application. Although the catalyst has multi-interface structural characteristics, good precious metal dispersion and many active sites, the multi-interface structural basis determines that the amount of precious metal used in the catalyst is relatively high, the catalyst preparation cost is high, and the prospects for industrial promotion are unclear.
[0006] Patent application CN1986035A discloses a method for purifying automobile exhaust gas. The catalyst can achieve the purification of CO, HC, NO at a relatively low ignition temperature. x However, to achieve the desired purification goal, more precious metals need to be used, and the active components will fall off the carrier after a period of use, causing the catalyst activity to drop rapidly or even deactivate.
[0007] Patent application CN1488435A discloses a catalytic combustion catalyst and a preparation method thereof. The catalyst has a high catalytic combustion organic waste gas conversion efficiency, but the coating is composed of a composite oxide formed by Al2O3, SiO2 and one or more alkaline earth metal oxides, uses a high content of precious metal elements, and has the disadvantages of being expensive, having poor anti-toxicity and poor general applicability.
[0008] Therefore, the development of highly efficient, inexpensive, environmentally friendly, and durable catalysts has become a research hotspot and application trend of catalytic oxidation catalysts at home and abroad. Summary of the invention
[0009] The purpose of the present invention is to efficiently remove carbon-based oxygen-containing molecular gases from tail gas discharged during chemical production processes, and to provide a monolithic noble metal catalyst and its preparation method and application. The present invention promotes the dispersion of active noble metals and the exposure of active phases by regulating the surface defect site structure of the monolithic catalyst; and efficiently constructs catalytic active sites on the catalyst surface, while reducing the content of active noble metals, increasing the adsorption capacity of carbon-based oxygen-containing molecular gases and oxygen, promoting the adsorption and activation of oxygen, and thus improving the catalytic efficiency of the catalyst.
[0010] In order to achieve the above-mentioned objectives, the present invention provides, on the one hand, an integral precious metal catalyst, comprising a porous regular carrier and an active component loaded on the porous regular carrier, wherein the active component contains precious metals and optional alloy metals, and the particle size of the active component is 1-8nm, preferably 2-6nm.
[0011] Preferably, the mesopore size of the monolithic noble metal catalyst is 0.1-20 nm, and the specific surface area is 200-800 m 2 / g.
[0012] Preferably, the content of the active component is 0.1-1 part by weight relative to 100 parts by weight of the porous structured carrier.
[0013] Preferably, the porous structured carrier is obtained by sequentially subjecting a structured carrier to acid treatment and calcination.
[0014] Preferably, the acid used in the acid treatment process is a mixed acid of nitric acid and sulfuric acid and / or hydrochloric acid, and the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid is 1:1-10.
[0015] Preferably, the calcination process is carried out under the conditions of 100-1000 ml / min air flow and 100-1000°C.
[0016] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0017] Preferably, in the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3.
[0018] Preferably, the noble metal is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, more preferably a combination of platinum and palladium.
[0019] Preferably, the alloy metal is at least one of Fe, La and Ce, more preferably a combination of La and Ce.
[0020] The second aspect of the present invention provides a method for preparing a monolithic noble metal catalyst, the method comprising the following steps:
[0021] (1) treating the structured support with acid and calcining the structured support in sequence to obtain a porous structured support;
[0022] (2) The porous structured support is immersed in a mixed solution containing a noble metal precursor and an optional structural additive, and then purged with a high-pressure air knife, dried, calcined and reduced in sequence.
[0023] Preferably, in step (1), the acid treatment process comprises: refluxing the structured carrier with a mixed acid solution, then washing it to neutrality and drying it.
[0024] Preferably, the mixed acid is a mixture of nitric acid and sulfuric acid and / or hydrochloric acid, and the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid is 1:1-10.
[0025] Preferably, the concentration of the mixed acid is 2-10 mol / L.
[0026] Preferably, the reflux treatment conditions include: a temperature of 50-90° C. and a time of 1-24 hours.
[0027] Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
[0028] Preferably, in step (1), the calcination process is carried out under the conditions of 100-1000 ml / min air flow and 100-1000°C.
[0029] Preferably, in step (2), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12.
[0030] Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, 2-hydroxyethylamine hexahydroxoplatinic acid (IV), platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0031] Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0032] Preferably, in step (2), the high-pressure air knife purging process adopts 1.5-2.5 MPa air knife purging.
[0033] Preferably, the calcination conditions include: a temperature of 200-300° C. and a time of 4-10 hours;
[0034] Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, or a mixed atmosphere of different CO concentrations.
[0035] Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
[0036] The third aspect of the present invention provides a monolithic noble metal catalyst prepared by the above method.
[0037] A fourth aspect of the present invention provides the use of the above-mentioned integral noble metal catalyst in catalytic oxidation of carbon-based oxygen-containing molecular gases.
[0038] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0039] (1) Compared with other catalytic oxidation technologies, the monolithic noble metal catalyst with defect sites formed by regular carrier pretreatment has higher oxygen adsorption and activation capabilities and higher catalytic oxidation efficiency;
[0040] (2) Compared with other catalytic oxidation technologies, this catalyst has greater mechanical strength and is suitable for high space velocity and large volume gas treatment conditions;
[0041] (3) Compared with other catalytic oxidation technologies, this catalyst does not require coating preparation, has the advantages of high active metal firmness, strong water resistance, and is conducive to continuous long-term operation;
[0042] (4) Compared with other catalytic oxidation technologies, this catalyst has a low active metal content and does not require coating, which greatly reduces operating costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 1 is a TEM image of the monolithic catalyst prepared in Example 1;
[0044] Figure 2 It is the SEM-Mapping picture of the integral catalyst prepared in Example 1. DETAILED DESCRIPTION
[0045] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0046] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0047] In the present invention, unless otherwise specified, the concentration "%" of a gas refers to "volume %"; the "space velocity" refers to "volume space velocity"; and the pressure refers to absolute pressure.
[0048] The monolithic noble metal catalyst of the present invention comprises a porous regular carrier and an active component loaded on the porous regular carrier, wherein the active component contains a noble metal and an optional alloy metal. In the present invention, the surface of the porous regular carrier has a uniformly distributed porous structure (i.e., a surface defect structure), and the active component is dispersed in the porous structure, so that the active component is dispersed more uniformly and the particle size is smaller. Specifically, the particle size of the active component is 1-8nm, preferably 2-6nm, and more preferably 2-3nm.
[0049] In the monolithic noble metal catalyst of the present invention, the mesopore size of the monolithic noble metal catalyst is 0.1-20 nm, preferably 0.5-12 nm; the specific surface area is 200-800 m 2 / g, preferably 300-600m 2 / g.
[0050] In the monolithic precious metal catalyst described in the present invention, the content of the active component can be 0.1-1 weight part relative to 100 weight parts of the porous regular carrier. Specifically, it can be 0.1 weight part, 0.2 weight part, 0.3 weight part, 0.4 weight part, 0.5 weight part, 0.6 weight part, 0.7 weight part, 0.8 weight part, 0.9 weight part or 1 weight part.
[0051] In the monolithic noble metal catalyst of the present invention, the porous structured carrier is obtained by sequentially subjecting the structured carrier to acid treatment and calcination.
[0052] In some preferred embodiments, the acid used in the acid treatment process is a mixed acid of nitric acid and sulfuric acid and / or hydrochloric acid, and the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid is 1:1-10. Specifically, the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid can be, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10. In the present invention, by adjusting the ratio of the mixed acid, the surface defect site structure of the porous regular carrier can be regulated, the catalytic active sites on the catalyst surface can be efficiently constructed, and the adsorption capacity of carbon-based oxygen-containing molecular gas and oxygen can be increased while reducing the content of the precious metal catalyst, promoting the adsorption and activation of oxygen, and thus improving the catalytic efficiency of the catalyst.
[0053] In other preferred embodiments, the calcining process is carried out under the conditions of 100-1000ml / min air flow (specifically, for example, 100ml / min, 200ml / min, 300ml / min, 400ml / min, 500ml / min, 600ml / min, 700ml / min, 800ml / min, 900ml / min or 1000ml / min), 100-1000°C temperature (specifically, for example, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C).
[0054] In the present invention, the structured carrier is preferably selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, and the most preferred one is a cordierite honeycomb carrier.
[0055] In the monolithic noble metal catalyst of the present invention, in the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3, preferably 1:0.15-0.2.
[0056] In the monolithic noble metal catalyst of the present invention, in the active component, the noble metal can be selected from at least one of ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. When the noble metal is a combination of platinum and palladium, the molar ratio of platinum to palladium can be 1:0.5-2, and most preferably 1:1.
[0057] In the monolithic noble metal catalyst of the present invention, in the active component, the alloy metal may be at least one of Fe, La and Ce, preferably a combination of La and Ce. When the alloy metal is a combination of La and Ce, the molar ratio of La to Ce may be 1:0.5-2, and most preferably 1:1.
[0058] The method for preparing the monolithic noble metal catalyst of the present invention comprises the following steps:
[0059] (1) treating the structured support with acid and calcining the structured support in sequence to obtain a porous structured support;
[0060] (2) The porous structured support is immersed in a mixed solution containing a noble metal precursor and an optional structural additive, and then subjected to high-pressure air knife purging, drying, calcination and reduction in sequence.
[0061] In step (1), the acid treatment process can remove impurities contained in the structured support to form a bare hydroxyl surface. The acid treatment process can include: refluxing the structured support with a mixed acid solution, then washing it to neutrality and drying it.
[0062] Specifically, the mixed acid is a mixture of nitric acid and sulfuric acid and / or hydrochloric acid, and the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid can be 1:1-10, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.
[0063] Specifically, the concentration of the mixed acid may be 2-10 mol / L, preferably 2-5 mol / L.
[0064] Specifically, the reflux treatment conditions may include: a temperature of 50-90° C. and a time of 1-24 hours.
[0065] In the method described in the present invention, the regular carrier can be selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier, preferably a cordierite honeycomb carrier.
[0066] In step (1), the calcination process is carried out under the conditions of 100-1000ml / min air flow (specifically, for example, 100ml / min, 200ml / min, 300ml / min, 400ml / min, 500ml / min, 600ml / min, 700ml / min, 800ml / min, 900ml / min or 1000ml / min) and 100-1000°C temperature (specifically, for example, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C).
[0067] In step (2), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12. Specifically, the pH value of the mixed solution can be 9, 10, 11 or 12, for example.
[0068] In the present invention, the noble metal in the noble metal precursor is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably a combination of platinum and palladium. In a specific embodiment, the noble metal precursor is selected from at least one of chloroplatinic acid, hexahydrooxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0069] In the present invention, the structural additive is added to provide alloy metals so that the active components in the prepared catalyst exist in the form of noble metal elements, alloys and noble metal oxides. In a specific embodiment, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
[0070] In step (2), the high-pressure air knife purging process adopts 1.5-2.5MPa air knife purging.
[0071] In step (2), the calcination conditions may include: a temperature of 200-300° C. and a time of 4-10 hours;
[0072] In step (2), the reducing atmosphere may be H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, and a mixed atmosphere of different CO concentrations. In a specific embodiment, the reducing atmosphere is a mixed atmosphere of different H2 concentrations and / or a mixed atmosphere of different CO concentrations, and the formation of surface oxygen vacancies of the catalyst is efficiently controlled by regulating the reducing atmosphere. Specifically, the reducing atmosphere may be, for example, 5% H2 (N2 dilution), 10% H2 (N2 dilution), 15% H2 (N2 dilution), 5% CO (N2 dilution), etc.
[0073] In step (2), the reduction conditions may include: a catalyst heating rate of 2-20° C. / min, a reduction temperature of 300-450° C., and a reduction time of 1-10 h.
[0074] In the method described in the present invention, the amount of various reaction raw materials used in steps (1) to (2) is such that in the prepared integral precious metal catalyst, the content of the active component can be 0.1-1 weight part, preferably 0.2-0.5 weight part, relative to 100 weight parts of the porous regular carrier.
[0075] The present invention also provides a monolithic noble metal catalyst prepared by the above method. In the monolithic noble metal catalyst, the surface defect structure of the monolithic catalyst is regulated to promote the dispersion of active components and exposure of active phases; and the catalytic active sites on the catalyst surface are efficiently constructed, while reducing the noble metal content, increasing the adsorption capacity of carbon-based oxygen-containing molecular gas and oxygen, promoting the adsorption and activation of oxygen, and thus improving the catalytic efficiency of the catalyst.
[0076] The present invention also provides the use of the above-mentioned integral noble metal catalyst in catalytic oxidation of carbon-based oxygen-containing molecular gas.
[0077] The following examples further illustrate the monolithic noble metal catalyst and its preparation method and application described in the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0078] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0079] Example 1
[0080] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0081] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined under 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0082] Next, 0.5 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 9 for 3 h to obtain solution 1.
[0083] The porous regular support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C drying oven for 12 hours, and then calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic noble metal catalyst Cat-1, wherein the content of active noble metal components was 0.35% by weight, the content of auxiliary agents was 3% by weight, the particle size of the active noble metal components was between 2.1-2.4nm, the mesopore channel size distribution was 3-4nm, and the specific surface area was about 400m 2 / g.
[0084] The TEM image and SEM-Mapping image of the monolithic noble metal catalyst are shown in Figure 1 and Figure 2 shown.
[0085] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 245℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0086] Example 2
[0087] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0088] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / hydrochloric acid (mixed acid ratio is 1:1), reflux at 90°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined at 500°C with an air flow of 1000 ml / min to obtain a porous regular carrier.
[0089] Next, 0.5 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 10 for 3 h to obtain solution 1.
[0090] The porous regular support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C drying oven for 12 hours, and then calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic noble metal catalyst Cat-2, wherein the content of active noble metal components was 0.35% by weight, the content of auxiliary agents was 3% by weight, the particle size of the active noble metal components was between 2.2-2.5nm, the mesopore channel size distribution was 10-12nm, and the specific surface area was about 300m 2 / g.
[0091] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 275℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0092] Example 3
[0093] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:5), reflux at 50°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined at 800°C with an air flow of 1000 ml / min to obtain a porous regular carrier.
[0094] Next, 0.5 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 12 for 3 h to obtain solution 1.
[0095] The porous structured support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C oven for 12 hours, and then calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic noble metal catalyst Cat-3, wherein the content of active noble metal components was 0.35% by weight, the content of auxiliary agents was 3% by weight, the particle size of the active noble metal components was between 2.6-2.8nm, the mesopore channel size distribution was 0.5-2nm, and the specific surface area was about 600m 2 / g.
[0096] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 295℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0097] Example 4
[0098] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0099] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 1 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined at 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0100] Next, 0.6 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (the molar ratio of platinum to palladium is 1.5:1) and 240 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (the molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 10 for 3 h to obtain a solution 1.
[0101] The porous regular support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C drying oven for 12 hours, and then calcined at 200°C for 10 hours. Then, it was reduced at 420°C (heating rate of 8°C / min) for 6 hours in an atmosphere of 10% H2 and 90% N2 to obtain a monolithic noble metal catalyst Cat-4, wherein the content of active noble metal components was 0.38% by weight, the content of auxiliary agents was 3.5% by weight, the particle size of the active noble metal components was between 2.2-2.3nm, the mesopore size distribution was 2-3nm, and the specific surface area was about 450m 2 / g.
[0102] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 235℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0103] Example 5
[0104] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0105] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 5 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined at 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0106] Next, 0.8 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (the molar ratio of platinum to palladium is 1:1.5) and 250 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (the molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 11 for 3 h to obtain a solution 1.
[0107] The porous structured support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a drying oven at 100°C for 12 hours, and then calcined at 220°C for 8 hours. Then, it was reduced at 380°C (heating rate of 12°C / min) for 7 hours in an atmosphere of 10% H2 and 90% N2 to obtain a monolithic noble metal catalyst Cat-5, wherein the content of active noble metal components was 0.51% by weight, the content of auxiliary agents was 3.8% by weight, the particle size of active noble metal components was between 2.5-2.6nm, the mesopore size distribution was 10-12nm, and the specific surface area was about 500m 2 / g.
[0108] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 305℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0109] Example 6
[0110] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0111] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined under 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0112] Next, 1 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 2:1) and 180 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 12 for 3 h to obtain solution 1.
[0113] The porous structured support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C oven for 12 hours, and then calcined at 250°C for 5 hours. Then, it was reduced at 360°C (heating rate of 15°C / min) for 10 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic noble metal catalyst Cat-6, wherein the content of active noble metal components was 0.63% by weight, the content of auxiliary agents was 2.5% by weight, the particle size of the active noble metal components was between 2.2-2.3nm, the mesopore size distribution was 2-2.5nm, and the specific surface area was about 430m 2 / g.
[0114] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 225℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0115] Example 7
[0116] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0117] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined at 500°C with an air flow of 1000 ml / min to obtain a porous regular carrier.
[0118] Next, 0.7 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:2) and 240 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:1) were stirred at 25° C. and pH 9 for 3 h to obtain solution 1.
[0119] The porous regular support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C drying oven for 12 hours, and then calcined at 280°C for 4 hours. Then, it was reduced at 320°C (heating rate of 18°C / min) for 9 hours in an atmosphere of 10% H2 and 90% N2 to obtain a monolithic noble metal catalyst Cat-7, wherein the content of active noble metal components was 0.45% by weight, the content of auxiliary agents was 3.6% by weight, the particle size of the active noble metal components was between 2.5-2.7nm, the mesopore size distribution was 3-4nm, and the specific surface area was about 400m 2 / g.
[0120] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 255℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 450h (i.e., the reaction was carried out continuously for 450h, and the catalytic activity of the catalyst did not decrease significantly).
[0121] Example 8
[0122] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0123] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined under 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0124] Next, 0.5 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 200 ml of a 1 mol / L ferric nitrate and zirconium nitrate mixed solution (molar ratio of iron to zirconium is 1:1) were stirred at 25° C. and pH 9 for 3 h to obtain solution 1.
[0125] The porous regular support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C drying oven for 12 hours, and then calcined at 250°C for 6 hours. Then, it was reduced at 400°C (heating rate of 10°C / min) for 5 hours in an atmosphere of 10% H2 and 90% N2 to obtain a monolithic noble metal catalyst Cat-8, wherein the content of active noble metal components was 0.35% by weight, the content of auxiliary agents was 3% by weight, the particle size of the active noble metal components was between 2.1-2.4 nm, the mesopore size distribution was 3-4 nm, and the specific surface area was about 400 m 2 / g.
[0126] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 315℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 350h (i.e., the reaction was carried out continuously for 350h, and the catalytic activity of the catalyst did not decrease significantly).
[0127] Example 9
[0128] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0129] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined under 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0130] Next, 0.7 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 220 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 2:1) were stirred at 25° C. and pH 10 for 3 h to obtain solution 1.
[0131] The porous structured support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C oven for 12 hours, and then calcined at 240°C for 7 hours. Then, it was reduced at 410°C (heating rate of 5°C / min) for 4 hours in a 10% H2, 90% N2 atmosphere to obtain a monolithic noble metal catalyst Cat-9, wherein the content of active noble metal components was 0.46% by weight, the content of auxiliary agents was 3.2% by weight, the particle size of the active noble metal components was between 2.5-2.7nm, the mesopore size distribution was 3-4nm, and the specific surface area was about 400m 2 / g.
[0132] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 325℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0133] Example 10
[0134] This example is used to illustrate the monolithic precious metal catalyst and its preparation method and application according to the present invention.
[0135] First, take a commercially available 200 cpsi, 100×100×50 mm cordierite honeycomb ceramic, use 2 mol / L nitric acid / sulfuric acid (mixed acid ratio of 1:10), reflux at 80°C for 24 hours, wash with deionized water to a pH value of 7, and dry to obtain an acid-treated regular carrier. The acid-treated regular carrier is calcined under 1000 ml / min air flow and 1000°C to obtain a porous regular carrier.
[0136] Next, 0.9 L of a 1 mol / L chloroplatinic acid and palladium chloride mixed solution (molar ratio of platinum to palladium is 1:1) and 250 ml of a 1 mol / L cerium nitrate and lanthanum nitrate mixed solution (molar ratio of cerium to lanthanum is 1:2) were stirred at 25° C. and pH 11 for 3 h to obtain solution 1.
[0137] The porous structured support was immersed in the solution 1, allowed to stand for 30 minutes, taken out and purged with a 2MPa air knife, dried in a 100°C oven for 12 hours, and then calcined at 260°C for 5 hours. Then, the support was reduced at 440°C (heating rate of 3°C / min) for 2 hours in an atmosphere of 10% H2 and 90% N2 to obtain a monolithic noble metal catalyst Cat-10, wherein the content of active noble metal components was 0.58% by weight, the content of auxiliary agents was 3.7% by weight, the particle size of the active noble metal components was between 2.5-2.8 nm, the mesopore size distribution was 3-4 nm, and the specific surface area was about 400 m 2 / g.
[0138] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature 300℃. Gas chromatograph was used to detect CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that CO≤100ppm, VOCs≤120ppm, conversion rate≥99%, and catalyst stability was 500h (i.e., the reaction was carried out continuously for 500h, and the catalytic activity of the catalyst did not decrease significantly).
[0139] Comparative Example 1
[0140] The monolithic precious metal catalyst prepared according to the method of Example 1 is different in that the cordierite honeycomb ceramic is not subjected to acid treatment and calcination, but is directly immersed in a mixed solution containing chloroplatinic acid, palladium chloride, cerium nitrate and lanthanum nitrate, and then purged with a high-pressure air knife, dried, calcined and reduced in sequence, thereby obtaining a monolithic precious metal catalyst Cat-D1, wherein the content of the active precious metal component is 0.05% by weight, the content of the auxiliary agent is 0.1% by weight, the particle size of the active precious metal component is between 2.1 and 2.3 nm, there is no mesopore, and the specific surface area is about 50 m 2 / g.
[0141] The catalyst was loaded into a fixed bed reactor, and the reaction raw gas consisted of 95% CO2, 4% CO, and 1% VOCs, with a reaction space velocity of 5000h -1 , reaction pressure 0.1MPa, reaction temperature ≥500℃. Gas chromatograph was used to detect the CO concentration and VOCs concentration at the reactor outlet. The reaction results showed that the CO concentration was about 5000ppm, the VOCs concentration was about 5000ppm, the conversion rate was ≤5%, and the catalyst stability was poor (less than 50h).
[0142] It can be seen from the above examples and comparative examples that the monolithic noble metal catalyst prepared in the present invention exhibits a good catalytic effect in the process of catalytic oxidation of carbon-based oxygen-containing molecular gases, and the catalyst stability is significantly better, and is suitable for continuous long-term operation.
[0143] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A monolithic noble metal catalyst, characterized in that: The invention comprises a porous regular carrier and an active component loaded on the porous regular carrier, wherein the active component contains a noble metal and an optional alloy metal, and the particle size of the active component is 1-8 nm, preferably 2-6 nm.
2. The monolithic noble metal catalyst according to claim 1, characterized in that: The monolithic noble metal catalyst has a mesoporous channel size of 0.1-20 nm and a specific surface area of 200-800 m 2 / g.
3. The monolithic noble metal catalyst according to claim 1 or 2, characterized in that: The content of the active component is 0.1-1 part by weight relative to 100 parts by weight of the porous structured carrier.
4. The monolithic noble metal catalyst according to any one of claims 1 to 3, characterized in that: The porous structured carrier is prepared by sequentially subjecting the structured carrier to acid treatment and calcination.
5. The monolithic noble metal catalyst according to claim 4, characterized in that: The acid used in the acid treatment process is a mixed acid of nitric acid and sulfuric acid and / or hydrochloric acid, and the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid is 1:1-10.
6. The monolithic noble metal catalyst according to claim 4, characterized in that: The calcination process is carried out under the conditions of 100-1000 ml / min air flow and 100-1000° C.
7. The monolithic noble metal catalyst according to any one of claims 4 to 6, characterized in that: The structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
8. The monolithic noble metal catalyst according to any one of claims 1 to 7, characterized in that: In the active component, the molar ratio of the noble metal to the alloy metal is 1:0.1-0.3; Preferably, the noble metal is at least one of silver, ruthenium, rhodium, palladium, osmium, iridium and platinum, more preferably a combination of platinum and palladium; Preferably, the alloy metal is at least one of Fe, La and Ce, more preferably a combination of La and Ce.
9. A method for preparing a monolithic noble metal catalyst, characterized in that: The method comprises the following steps: (1) treating the structured support with acid and calcining the structured support in sequence to obtain a porous structured support; (2) The porous structured support is immersed in a mixed solution containing a noble metal precursor and an optional structural additive, and then purged with a high-pressure air knife, dried, calcined and reduced in sequence.
10. The method according to claim 9, characterized in that In step (1), the acid treatment process includes: refluxing the structured carrier with a mixed acid solution, then washing it to neutrality and drying it; Preferably, the mixed acid is a mixture of nitric acid and sulfuric acid and / or hydrochloric acid, and the molar ratio of nitric acid to sulfuric acid and / or hydrochloric acid is 1:1-10; Preferably, the concentration of the mixed acid is 2-10 mol / L; Preferably, the conditions of the reflux treatment include: a temperature of 50-90° C. and a time of 1-24 hours; Preferably, the structured carrier is selected from at least one of a cordierite honeycomb carrier, a mullite honeycomb carrier, a diamond honeycomb carrier, a corundum honeycomb carrier, a zirconium corundum honeycomb carrier, a quartz honeycomb carrier, a nepheline honeycomb carrier, a feldspar honeycomb carrier and an alumina honeycomb carrier.
11. The method according to claim 9 or 10, characterized in that: In step (1), the calcination process is carried out under the conditions of 100-1000 ml / min air flow and 100-1000°C.
12. The method according to claim 9, characterized in that In step (2), the pH value of the mixed solution containing the noble metal precursor and the structural additive is 9-12; Preferably, the noble metal precursor is selected from at least one of chloroplatinic acid, hexahydroxoplatinic acid (IV) 2-hydroxyethylamine salt, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate; Preferably, the structural additive is selected from at least one of ferric nitrate, cerium nitrate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, cerium sulfate and cerium trioxide.
13. The method according to claim 9 or 12, characterized in that: In step (2), the high-pressure air knife purging process is performed by using 1.5-2.5 MPa air knife purging; Preferably, the calcination conditions include: a temperature of 200-300° C. and a time of 4-10 hours; Preferably, during the reduction process, the reducing atmosphere is H2, CO, a combination of H2 and CO, a mixed atmosphere of different hydrogen concentrations, or a mixed atmosphere of different CO concentrations; Preferably, the reduction conditions include: catalyst heating rate of 2-20°C / min, reduction temperature of 300-450°C, and reduction time of 1-10h.
14. A monolithic noble metal catalyst prepared by the method according to any one of claims 9 to 13.
15. Use of the integral noble metal catalyst according to any one of claims 1 to 8 and 14 in catalytic oxidation of carbon-based oxygen-containing molecular gases.
Citation Information
Patent Citations
Preparation method of carbon monoxide low-temperature catalytic oxidation catalyst
CN113996284A
PtCo / Co3O4-x-Al2O3 multi-interface structure catalyst as well as preparation method and application thereof
CN114308063A
Catalytic combustion catalyst and preparing method thereof
CN1488435A
Automobile exhaust gas purifying process
CN1986035A
Preparation method of noble metal loaded whole catalyst with magnesia-alumina meso-porous composite oxides
CN101391233A